Investigação dos mecanismos de ação da atividade gastroprotetora de 1,4-cineol em modelos de úlcera gástrica em camundongos - Feitosa, Mariana Lima (2011)
1,4-Cineole is a widely distributed monoterpene ether, which is one of the flavor constituents of lime juice. The aim of this work was to evaluate the gastroprotective effect of 1,4-Cineole (CIN 100 and 200 mg/Kg) on ethanol or piroxicam-induced lesions in mice and further investigate the possible pharmacological mechanisms involved in this action. The oral administration of 1,4-cineole 200 mg/kg was able to protect the gastric mucosa from ethanol injury (0.2 ml/animal, p.o.). This gastroprotection was also evaluated microscopically showing that CIN (200 mg/kg, p.o.) decreased the cell loss in the mucosa, submucosal edema, inflammatory infiltration and hemorrhage. 1,4-Cineole (100 and 200 mg/kg, p.o.) also reduced significantly the gastric lesions induced by piroxicam (30 mg/kg, s.c.). Gastroprotective mechanism of CIN was examined in the dose of 200 mg/kg, in the model of gastric lesions induced by ethanol in mice. In animals pretreated with L-NAME (10 mg/kg, i.p.), an inhibitor of nitric oxide synthase, or with glibenclamide (10 mg/kg, i.p.), a drug that blocks ATP-dependent potassium channels, or with capsazepine (5 mg/kg, i.p.), an antagonist of vanilloid receptor TRPV-1, the gastroprotective effect of CIN was not inhibited significantly, suggesting that the effect of CIN is not involved with this mechanisms. Otherwise, the gastroprotective effect of CIN (200 mg/kg, p.o.) was reverted in animals pretreated with indomethacin (10 mg/kg, p.o.), a nonselective inhibitor of cyclooxygenase, demonstrating that there is activation of these enzymes in the mechanism of action of CIN. This work also evaluated the antioxidant mechanism of CIN as gastroprotective agent against ethanol-induced lesions. Under our experimental conditions, the model of induction of ethanol injury caused changes in the antioxidant system of the gastric mucosa of mice as the decrease in the levels of sulfhydryl groups (GSH) and activity of superoxide dismutase (SOD), also showed increased activity of myeloperoxidase (MPO) and high concentration of species that react with thiobarbituric acid (TBARS) as index of lipid peroxidation (LPO). 1,4-Cineole (200 mg/kg, p.o.) in the model of ethanol did not interfere with the concentration of GSH, but allowed the restoration of normal SOD activity, normal levels of LPO and MPO activity. The data suggest that CIN 100 and 200 mg/kg promote gastroprotection against lesions induced by ethanol or piroxicam in mice whose mechanisms include the involvement of endogenous prostaglandins and potent antioxidant activity.